Influence of mouthwashes on extended exhaled nitric oxide (FENO) analysis. (18th August 2018) - Lassmann-Klee, Paul Guenther; Lehtimäki, Lauri; Lindholm, Tuula; Malmberg, L. Pekka; Sovijärvi, Anssi Raimo Antero; Piirilä, Päivi
Abstract: Fractional exhaled nitric oxide ( F ENO ) is used to assess eosinophilic inflammation of the airways. F ENO values are influenced by the expiratory flow rate and orally produced NO. We measured F ENO at four different expiratory flow levels after two different mouthwashes: tap water and carbonated water. Further, we compared the alveolar NO concentration ( C ANO ), maximum airway NO flux ( J ′awNO ) and airway NO diffusion ( D awNO ) after these two mouthwashes. F ENO was measured in 30 volunteers (healthy or asthmatic) with a chemiluminescence NO-analyser at flow rates of 30, 50, 100 and 300 mL/s. A mouthwash was performed before the measurement at every flow rate. The carbonated water mouthwash significantly reduced F ENO compared to the tap water mouthwash at all expiratory flows: 50 mL/s ( p <  .001), 30 mL/s ( p =  .001), 100 mL/s ( p <  .001) and 300 mL/s ( p =  .004). J ′awNO was also significantly reduced ( p =  .017), however, there were no significant differences in C ANO and D awNO . In conclusion, a carbonated water mouthwash can significantly reduce oropharyngeal NO compared to a tap water mouthwash at expiratory flows of 30–300 mL/s without affecting the C ANO and D awNO . Therefore, mouthwashes need to be taken into account when comparing F ENO results.